Pattern and person : ornament, society, and self in classical China - Powers, Martin Joseph, 1949- (Harvard East Asian monographs, 2006)
"In Classical China, crafted artifacts offered a material substrate for abstract thought, as graphic paradigms for social relationships. Focusing on the 5th to 2nd centuries B.C., Martin Powers explores how these paradigms continued to inform social thought long after the material substrate had been abandoned. In this detailed study, the author makes the claim that artifacts are never neutral: as distinctive possessions, each object - through the abstracting function of style - offers a material template for scales of value. Likewise, through style, pictorial forms can make claims about material "referents," the things depicted. By manipulating these scales and their referents, artifacts can shape the way status, social role, or identity is understood and enforced. The result is a kind of "spatial epistemology" within which the identities of persons are constructed. Powers thereby posits a relationship between art and society that operates at a level deeper than iconography, attributes, or social institutions."--Jacket